Comparing Same-Sex Marriage in Australia and Canada: Institutions and Political Will. Issue 1 (23rd November 2016) - Johnson, Carol; Tremblay, Manon
Abstract : This article explores why there have been such different trajectories in regard to same-sex marriage in Australia and Canada. Canada was one of the first countries to introduce same-sex marriage (in 2005) and, at time of writing, Australia still had not done so. 1 The comparison is particularly interesting given that Australia and Canada have relatively similar political institutions except that Australia has no Charter of Rights. Miriam Smith has suggested that institutional factors explain the different trajectories of policies on same-sex marriage in Canada and the US. However, the shift in comparative lens to Canada and Australia provides new insights into the key role of factors influencing 'political will' in regard to same-sex marriage in both countries. Those multiple influences do include institutions but also the role played by party electoral strategies. Consequently, the article provides insights into the factors that can influence minority group rights in different national democratic settings.